Fern nothogenera and ×Lepinema, a new hybrid genus between Ellipinema and Lepisorus (Polypodiaceae) - Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2020)
The biological species concept is not exclusively applicable in many groups of organisms including ferns. Interspecific fern hybrids are not rare: there are 16 intergeneric hybrid genera in ferns confirmed with molecular data. Here we add one more hybrid genus in the tribe Lepisoreae of Polypodiaceae, ×Lepinema, formed via hybridization between parents in two genera: Ellipinema and Lepisorus.